Study on the Phenology of Three Fruit Trees Species in Purwodadi Botanical Gardens, East Java, and Its Relationship with Mesoclimates - Agung Sri Darmayanti; Ariffin; Budi Waluyo; Endang Arisoesilaningsih (Institut Pertanian Bogor (IPB University), 2023)
Nowadays the study of phenology has taken an important contribution to climate change research. Therefore this study observed local fruit trees species collected in the Purwodadi Botanical Gardens (PBG); they were Flacourtia rukam (Zoll & Moritzi), Limonia acidissima L., and Manilkara kauki (L) Dubard. We used fruit phenology data from 2014 to 2018 as secondary data to describe the changes. We also observed the weekly phenology of flowering and fruiting for three years from 2019 to 2022. At the same time, mesoclimates components included precipitation, maximum and minimum temperature were daily recorded by the PBG weather station measurement. Data pairs were then analyzed by using a structural modeling of WarpPLS to determine the relationship among mesoclimates and phenology variables. Research showed that phenology of flowering and fruiting of F. rukam, L. acidisissima, and M. kauki was significantly shifted from 2014 to 2022, along with changes in rainfall patterns, maximum and minimum temperatures in the PBG. Based on the Friedman test, it was shown that the maximum and minimum temperatures significantly changed (p<0.05). Five months of mesoclimates were significant predictors and affected before the measurement of phenological flowering and fruiting of three species. High precipitation significantly reduced maximum temperature, and increased minimum temperature. The high precipitation reduced the probability of flowering and fruiting initiation, except for those of L. acidissima. Increasing maximum temperature reduced flower and fruit set of F. rukam and L. acidisissima, while it reduced flowering of L. acidissima. Furthermore, minimum temperature induced flowering, except in L. acidissima.